Case study focusing on services provided by Globalart Bandar Sierra in Kota Kinabalu, Sabah / Susilawaty Inderan - Inderan, Susilawaty (Universiti Teknologi MARA, Sabah, 2021)
Customer service quality should be in good performance in each firm. The excellent customers service are very crucial in order to satisfy the customers by continuously monitor the performance of customer service as it will reveal the level of customers satisfaction towards the service provided to them. Customers service quality in Globalart Bandar Sierra is always having problem such as employee late to respond from customers related with services provided and employee did not give enough details about information related. These are including on how they build the customer satisfaction loyalty and doing market share. This is the one of reason why they hard to achieve target market. There are no stable marketing strategy to attract customers join in their service. Although the communication workers to customers are not in the proper ways. This is because a good communication skills should be apply to show a good customers service quality in each company. Thus, this research would like to identify the solution for the service issues encounter by Globalart Bandar Sierra so hat the company able to enhance their service performance and the customers experience.